2022
DOI: 10.1039/d1ra07864j
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of photoelectric behaviors of silver sulfide particles in different surroundings

Abstract: Photocurrent of Ag2S particles decreases in alcohol gases or with CuPc coating and increases in CS2. This interesting phenomenon is explained through a model of gas adsorption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 44 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…Actually, researches on Ag 2 S-based optical sensing devices have been conducted. 24,25) We thought that local light irradiation to a Ag 2 S island network reservoir promotes the growth and contraction of Ag filaments between Ag 2 S islands in a light-irradiated area, which modifies a network of conductive channels. In this study, we confirmed the function and applied it to develop a physical reservoir with optical sensing capability for optical pattern classification.…”
Section: Introductionmentioning
confidence: 99%
“…Actually, researches on Ag 2 S-based optical sensing devices have been conducted. 24,25) We thought that local light irradiation to a Ag 2 S island network reservoir promotes the growth and contraction of Ag filaments between Ag 2 S islands in a light-irradiated area, which modifies a network of conductive channels. In this study, we confirmed the function and applied it to develop a physical reservoir with optical sensing capability for optical pattern classification.…”
Section: Introductionmentioning
confidence: 99%
“…The Schottky rectifying effect is caused by the pn junction space charge field formed at the Ag 2 S/Cu 3 P interface. The conduction type of n-Ag 2 S and p-Cu 3 P was proved by hot-probe method [ 20 , 21 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…5 a shows the I–V curves of the Ag 2 S/Cu 3 P structure with Ag 2 S layer being heated. The cross point of the figure- 8 shape deviates towards positive voltage, which is due to the Seebeck effect [ 25 ]. The resistances both of HRS and LRS decrease with the rise of temperature ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, several studies have been conducted on Ag 2 S-based optical sensing devices. 33,34) We have previously demonstrated that direct light irradiation to a physical reservoir made of a Ag 2 S island network changes the properties of nonlinear transformations and memory capacity, thereby enabling the classification of optical patterns. 35) We believe that local photoexcitation changes the electronic conduction properties within the network, which also changes the distribution of silver ions within each Ag 2 S island.…”
Section: Introductionmentioning
confidence: 99%